Arctic Shipping Development Prospects Evaluation: Nuclear Icebreaker Fleet in the Northern Sea Route. - Khomiakova, Dr.Tatiana (2011)
Dr.Tatiana Khomiakova, Academy of National Economy, Russia, at the NRF 6th open Assembly in Hveragerði, Iceland. September 2011.